Introduksi Mesin Pencacah Limbah Organik Portabel Tenaga Surya di Lahan Pertanian Jagung Desa Longalo - Ashari, Ulfira; Tamrin, Moh. Muhrim; Putra Surusa, Frengki Eka; Jafar, Muhammad Iqbal (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
Corn is a leading commodity for farmers in Longalo Village, North Bulango District, Bone Regency, however, in encouraging increased agricultural productivity in Longalo Village, there are obstacles related to the limited amount of fertilizer available for agricultural cultivation activities in Longalo Village. On the other hand, agricultural activities in Longalo Village produce waste such as corn litter, rice straw, coconut shells, cocoa pod skins, these plant trimmings have the potential to be used as organic fertilizer, but most organic agricultural waste is burned or thrown away, which has an impact on the ecology and public health. Apart from that, there is no knowledge among farmer groups regarding technological innovations in efficient, effective and economical chopping machines that make it easier to speed up the process of processing organic waste into fertilizer using new, renewable energy, which has caused problems in Longalo Village to become more protracted, therefore the introduction of waste chopping machines Portable organic solar power on land is one way out to overcome the obstacles faced by corn farmers in Longalo Village, North Bulango District, Bone Bolango Regency.